Potential pathways for natural active ingredients to intervene in diabetic kidney disease: targeting macrophage infiltration - Yan, Yan; Wang, Wenru; Chen, Yao; Zhao, Keqin; Zhan, Tian; Song, Xuemin; Yang, Jiayi; Liu, Peng; Yu, Renhuan; Wang, Gang (Frontiers in Physiology, 2025)
Diabetic kidney disease (DKD), a grave microvascular complication of diabetes, is the primary cause of end-stage renal disease. Despite advances in conventional therapies, their limited efficacy underscores the urgent need for novel, multi-target intervention strategies. Macrophage infiltration and the subsequent chronic microinflammation are central to the pathogenesis of renal injury in DKD. A diverse array of natural bioactive compounds are emerging as promising therapeutic agents, capable of modulating these inflammatory pathways. This review investigates the mechanisms underlying the attenuation of DKD progression by six major classes of natural compounds, such as glycosides, diterpenoids, and alkaloids, among others, through the targeting of macrophage infiltration. Collectively, this synthesis offers a compelling case for developing natural product-based, multiple-target strategies to combat DKD. Collectively, this synthesis builds a compelling case for developing multi-target therapeutic strategies derived from natural products to combat DKD.